Estudo do efeito da composição e da nanoestrutura de nanopartículas de 'PT''NI' suportadas em carbono na eletrocatálise da reação de redução do oxigênio - Ometto, Felipe Berto [UNESP] (2014)
This study aimed to contribute to the development of materials with good performance for the catalysis of the oxygen reduction reaction, which occurs at the cathodes of fuel cells, by studying the influence of composition and nanostructure of carbon-supported PtNi nanoparticles on the electrocatalytic activity. The studies involved the preparation of catalysts containing PtNi nanoparticles of different compositions by the modified polyol method. Parts of these materials were submitted to a heat treatment in hydrogen at 300 °C aiming to promote an increase of the incorporation of Ni into the Pt lattice without causing severe changes on the size and distribution of particles on the support. The physical properties of the materials were evaluated by X-ray diffraction and transmission electron microscopy. The results showed that PtNi catalysts have a high degree of alloying and that particle distribution on the carbon support has good homogeneity. The electronic properties were evaluated in situ by X-ray absorption spectroscopy. The electrocatalytic activity for the oxygen reduction reaction was studied by the rotating ring disk technique. In acid medium, the presence of Ni in the catalysts causes an increase in the Pt 5d band, while the heat treatment resulted in a Pt 5d band vacancy decrease. A catalytic activity for PtNi materials higher than that of Pt was verified. In alkaline medium, the catalysts containing Ni showed a Pt 5d band more filled, probably resulting from the formation of Ni oxides. In general, Pt Ni catalysts are less active than Pt in alkaline medium. The tolerance to the presence of methanol was evaluated by comparing the polarization curves obtained in acid and alkaline solutions containing alcohol. A decrease of catalytic activity in the presence of methanol in acid medium and good tolerance in alkaline medium were observed.